2019
DOI: 10.1161/strokeaha.118.024651
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Utilization of Thrombectomy for Acute Stroke

Abstract: Background and Purpose— Racial and ethnic disparities in the access to mechanical thrombectomy (MT) for treatment of acute ischemic stroke (AIS) secondary to large vessel occlusion have been previously described. The effect of recent randomized trials validating MT as an effective therapy for AIS secondary to large vessel occlusion on such disparities has not been investigated. Methods— Information on admissions for AIS to endovascular centers occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 18 publications
2
77
8
Order By: Relevance
“…28, 29, and Table 1). While remarkably effective, these treatments can be administered to fewer than 10% of stroke patients because of exclusion criteria, hemorrhagic complications, and highly specialized resources required for thrombectomy (30). However, advances in imaging the penumbra may provide the opportunity to rescue salvageable tissue using noninterventional means.…”
Section: Intravascular Inflammatory Eventsmentioning
confidence: 99%
“…28, 29, and Table 1). While remarkably effective, these treatments can be administered to fewer than 10% of stroke patients because of exclusion criteria, hemorrhagic complications, and highly specialized resources required for thrombectomy (30). However, advances in imaging the penumbra may provide the opportunity to rescue salvageable tissue using noninterventional means.…”
Section: Intravascular Inflammatory Eventsmentioning
confidence: 99%
“…However, recent nationwide studies have demonstrated racial and ethnic disparities in the use of mechanical thrombectomy for stroke. 1,28,29 These studies acknowledge that the disparity in use of mechanical thrombectomy may be attributed to preadmission factors, such as delayed time from stroke onset to hospital presentation. Our results show that the mean time from stroke onset to hospital presentation for Black patients was almost twice that for White patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies have demonstrated a racial disparity in the use of thrombectomy and outcomes among patients with acute stroke after an emergent large-vessel occlusion. 1,28,29 The identification and correction of the sources of this disparity are essential. In this study, we compared stroke outcomes between Black and White patients who underwent mechanical thrombectomy for a stroke at our institution.…”
mentioning
confidence: 99%
“…Despite a series of clinical trials with neuroprotective drugs, current treatment options remain limited to thrombolysis and mechanical recanalization for the acute phase of ischemic stroke ( Powers, 2019 ). While effective, the treatments can only be applied to less than 10% of patients for a narrow treatment time window and strict exclusion criteria ( Rinaldo et al, 2019 ). Moreover, even a successful recanalization may lead to enlarged infarction due to ischemic-reperfusion (IR) injury ( Mizuma et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%